2016
DOI: 10.1371/journal.pgen.1005809
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Sumoylation of a Conserved Transcription Corepressor Prevents Persistent Inclusion Formation during Hyperosmotic Stress

Abstract: Cells are often exposed to physical or chemical stresses that can damage the structures of essential biomolecules. Stress-induced cellular damage can become deleterious if not managed appropriately. Rapid and adaptive responses to stresses are therefore crucial for cell survival. In eukaryotic cells, different stresses trigger post-translational modification of proteins with the small ubiquitin-like modifier SUMO. However, the specific regulatory roles of sumoylation in each stress response are not well unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 78 publications
(128 reference statements)
4
50
0
Order By: Relevance
“…S1A and Dataset S1), such as the transcriptional activators Gcn4 and Rap1 and the transcriptional repressors Tup1 and Cyc8 (Fig. 1B), which we and others have previously shown to be SUMO targets (10)(11)(12). The vast majority of proteins in group 2 are involved in cellular processes that ultimately impinge upon mRNA translation ( Fig.…”
Section: Significancementioning
confidence: 86%
See 1 more Smart Citation
“…S1A and Dataset S1), such as the transcriptional activators Gcn4 and Rap1 and the transcriptional repressors Tup1 and Cyc8 (Fig. 1B), which we and others have previously shown to be SUMO targets (10)(11)(12). The vast majority of proteins in group 2 are involved in cellular processes that ultimately impinge upon mRNA translation ( Fig.…”
Section: Significancementioning
confidence: 86%
“…Pull-downs in denaturing conditions were performed as previously described (10,11,29) with minor modifications (SI Methods).…”
Section: Methodsmentioning
confidence: 99%
“…A few examples include the ability of sumoylation to prevent protein inclusions formed by the transcriptional corepressor subunit Cyc8, to solubilize DNA end resection protein Sae2, and to reduce aggregation of translation factor CPEB3 or transcription factor androgen receptor (Drisaldi et al, 2015; Mukherjee et al, 2009; Oeser et al, 2016; Sarangi et al, 2015). Future study on how SUMO contributes to the dynamic assembly and disassembly of other proteinaceous and membraneless structures will expand our understanding of the structural roles of SUMO.…”
Section: Sumo Affects Nuclear Structures and Functionsmentioning
confidence: 99%
“…Interestingly, Gardner and coworkers recently showed that the conserved transcriptional corepressor Cyc8 is SUMOylated upon hyperosmotic stress in yeast (94). Loss of Cyc8 SUMOylation leads to cytoplasmic inclusion formation of this protein.…”
Section: Sumoylation Regulates Proteostasis At the Chromatin Levelmentioning
confidence: 99%
“…Loss of Cyc8 SUMOylation leads to cytoplasmic inclusion formation of this protein. Thus, SUMO acts to maintain the proper function of Cyc8 during hyperosmotic stress (94). This provides an interesting example of the role of SUMO during stress to maintain the solubility and thereby the function of these proteins.…”
Section: Sumoylation Regulates Proteostasis At the Chromatin Levelmentioning
confidence: 99%